The night albums : visibility and the ephemeral photograph - Albers, Kate Palmer, 1974- (University of California Press, 2021)
"We live in an era of abundant photography. It may then seem counterintuitive to study photographs that disappear or are difficult to discern, but Kate Palmer Albers argues that it is precisely this current cultural moment that allows us to recognize what has always been a basic and foundational, yet unseen, condition of photography: its ephemerality. Through a series of case studies spanning the history of photography, The Night Albums takes up the provocations of artists who collectively redefine how we experience visibility. From the protracted hesitancies of photography's origins, to conceptual and performative art that has emerged since the 1960s, and to the waves of technological experimentation flourishing today, Albers foregrounds artists who offer fleeting, hidden, conditional, and future modes of visibility. By unveiling how ephemerality shapes the photographic experience, she ultimately proposes an expanded framework for the medium"--